Coordinating External Manufacturing of Product Modules*. (23rd December 2015) - Persson, Magnus; Eklind, Martin Jan; Winroth, Mats
ABSTRACT: Product modularization has changed gradually from mainly being a way to bring strategic flexibility into product design, to becoming a means to reach new suppliers in a globalized world. Use of external suppliers is facilitated by the "embedded coordination" brought by standardized module interfaces which reduce the interdependence between modules manufactured by different suppliers. However, the distance between design and manufacturing is increased by heavy reliance on suppliers, and requires coordination between design and manufacturing. Hence, this article aims to identify appropriate mechanisms to enable coordination of external manufacturing of product modules. The investigation is based on two case studies in one manufacturing company that has for long relied heavily on external suppliers. The case studies identify different means, coordination mechanisms, of handling the increased distance between design and manufacturing. In addition to organizational solutions, various intermediaries including especially the supply chain function act as bridges between design and manufacturing. The appropriate mechanism to use is decided by the character of the product and the degree of upgrading. We recommend openness to adaptation to situation dynamics rather than investment in optimizing the level of integration with a particular supplier.